HOW DO MUSLIM WOMEN ENTREPRENEURS ACHIEVE SUSTAINABLE BUSINESS PERFORMANCE? THE INFLUENCE OF SOCIAL SUPPORT, RELIGIOSITY, AND GENDER STEREOTYPES (International Journal of Islamic Business, 2025)
From an Islamic perspective, entrepreneurship has been an essential activity for a long time. It started at the beginning of human life on this earth and continues to grow rapidly along with the development of human life itself. The interpretation and discussion of entrepreneurship from a capitalist and developed nation point of view has caused many researchers and practitioners in the world, including Malaysia, to prioritize the opinions of Western thinkers in evaluating business performance. Thus, this study aims to examine the influence of social support, religiosity, and gender stereotypes on the sustainable business performance of Muslim women entrepreneurs in the informal sector. This study selected women entrepreneurs based on cluster and purposive sampling techniques. Data processing using the structural equation modeling (SEM) method with the help of AMOS software. The study findings show that social support, religiosity, and gender stereotypes significantly predict social, economic, and environmental performance. The study findings hope to assist the relevant ministries and agencies in formulating an action plan to increase Muslim women's involvement in entrepreneurship. In addition, this study can also be referred to as an aid to the ministry in planning and designing programs needed by Muslim women entrepreneurs to help improve their ability to operate a business.